Predicting Compliance with Sanitary Behaviors among Students in Higher Education During the Second COVID-19 Wave: The Role of Health Anxiety and Risk Perception - Sarah Dekeyser; Emilie Schmits; Fabienne Glowacz; Olivier Klein; Mathias Schmitz; Robin Wollast; Vincent Yzerbyt; Olivier Luminet (Psychologica Belgica, 2023)
To limit the spread of COVID-19, public authorities have recommended sanitary behaviors such as handwashing, mask-wearing, physical distancing, and social distancing. We recruited a large sample of higher education students in Belgium ('N' = 3201–3441) to investigate the role of sociodemographic variables, mental health, previous COVID-19 infections, academic involvement, and risk perception on adherence to these sanitary behaviors. This cross-sectional study took place during the second COVID-19 wave in Belgium, between February and March 2021. Analyses showed that living alone, being female, later in the academic curriculum, having higher general and health anxiety, higher academic involvement, and higher risk perception were positively associated with adherence to the four aforementioned sanitary behaviors. Conversely, previous infection with COVID-19 and having been quarantined were negative predictors. Our results show a set of predictors highly similar for the four sanitary behaviors. We discuss potential initiatives to increase adherence to sanitary behaviors in this group of highly educated youngsters.